Negative electrode sheet and battery

CN122370324BActive Publication Date: 2026-10-20CALB GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610824368.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-20
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种负极片和电池,以解决现有技术中的硅基负极材料易发生膨胀导致电池的性能降低的问题

Benefits of technology

[0007]应用本发明的技术方案,通过综合控制负极片浮硅含量a和特定区域的压实密度b两者之间满足关系式(I),综合改善电池的动力学性能和能量密度。上述关系式(I)取值过大时,浮硅含量越高,由于浮硅缺乏碳骨架的缓冲和约束,其膨胀更加剧烈,容易在充放电过程中产生较大的界面应力,同时还可能引发晶格畸变,降低锂化反应动力学速率,或者靠近极耳侧的区域压实密度增加,锂离子从电解液向极片内部扩散受阻,电池的DCR增加;关系式(I)取值过小时,硅含量越低,导致负极片的克容量降低,或者靠近极耳侧区域的压实密度越小,负极活性材料减少,电池能量密度低。相比于其它范围,将关系式(I)的范围限定在本申请特定范围内能够有效调整浮硅含量与压实密度之间的相互作用,在抑制硅膨胀和提高负极片能量密度之间实现平衡,从而综合改善电池的动力学性能和能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122370324B_ABST
    Figure CN122370324B_ABST
Patent Text Reader

Abstract

The application provides a negative electrode sheet and a battery. The negative electrode sheet comprises a current collector, a negative material layer arranged on the surface of the current collector, and a plurality of tabs connected with one side of the current collector, the material of the negative material layer comprises a negative material, the negative material comprises a silicon-based material, along the leading direction of the tab, the part of the negative material layer close to the tab is a first area, the part of the negative material layer away from the tab is a second area, the compaction density of the negative material layer of the first area is less than the compaction density of the negative material layer of the second area; the curve of the mass of the negative material layer changing with temperature is measured by a thermogravimetric analysis test, in the curve, the change rate of the mass measured at the test end and the mass measured under the condition of 800 DEG C is the floating silicon content in the negative material layer, denoted as a; the compaction density of the negative material layer of the first area is b g / m 3 ; a and b satisfy the relationship: 0.13 <= a x b x 100 <= 13.6 (I).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a negative electrode and a battery. Background Technology

[0002] In the current field of battery technology, especially in the research and development of lithium-ion batteries, silicon-based materials have attracted much attention due to their high theoretical capacity, becoming one of the ideal candidates for anode materials. However, compared with traditional graphite-based anode materials, silicon-based materials exhibit significant volume change characteristics during lithium-ion insertion and extraction. This characteristic not only leads to a decrease in battery cycle stability but also causes degradation in kinetic performance, specifically manifested as a decrease in lithium-ion transport efficiency and an increase in battery internal resistance.

[0003] Based on this, it is of great significance to research and develop a negative electrode that is not prone to expansion and can improve the cycle stability and kinetic performance of batteries. Summary of the Invention

[0004] The main objective of this invention is to provide a negative electrode sheet and a battery to solve the problem that silicon-based negative electrode materials in the prior art are prone to expansion, which leads to a decrease in battery performance.

[0005] To achieve the above objectives, according to a first aspect of the present invention, a negative electrode sheet is provided, comprising a current collector, a negative electrode material layer disposed on the surface of the current collector, and a plurality of tabs connected to one side of the current collector. The material of the negative electrode material layer includes a negative electrode material, which includes a silicon-based material. Along the lead-out direction of the tabs, the portion of the negative electrode material layer near the tabs is a first region, and the portion of the negative electrode material layer away from the tabs is a second region. The compaction density of the negative electrode material layer in the first region is less than that in the second region. A curve showing the change in mass of the negative electrode material layer with temperature is obtained by thermogravimetric analysis. In the curve, the rate of change between the mass measured at the test endpoint and the mass measured at 800°C is the floating silicon content in the negative electrode material layer, denoted as a. The compaction density of the negative electrode layer in the first region is b g / m³. 3 ; a and b satisfy the relationship: 0.13≤a×b×100≤13.6 (I).

[0006] To achieve the above objectives, according to a second aspect of the present invention, a battery is provided, comprising a positive electrode, a separator, and a negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application.

[0007] By applying the technical solution of this invention, the dynamic performance and energy density of the battery are comprehensively improved by comprehensively controlling the relationship between the floating silicon content 'a' and the compaction density 'b' in a specific region of the negative electrode sheet, as expressed in Equation (I). When the value of Equation (I) is too large, the floating silicon content is higher. Due to the lack of buffering and constraint from the carbon skeleton, the floating silicon expands more violently, easily generating large interfacial stress during charging and discharging. It may also cause lattice distortion, reduce the kinetic rate of the lithiation reaction, or increase the compaction density in the region near the tab side, hindering the diffusion of lithium ions from the electrolyte to the electrode sheet, thus increasing the battery's DCR. When the value of Equation (I) is too small, the silicon content is lower, leading to a decrease in the specific capacity of the negative electrode sheet, or a smaller compaction density in the region near the tab side, resulting in less active material in the negative electrode and a lower battery energy density. Compared to other ranges, limiting the range of Equation (I) to the specific range of this application can effectively adjust the interaction between the floating silicon content and the compaction density, achieving a balance between suppressing silicon expansion and increasing the energy density of the negative electrode sheet, thereby comprehensively improving the dynamic performance and energy density of the battery. Attached Figure Description

[0008] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0009] Figure 1 This is a schematic diagram showing the unfolded view of the negative electrode obtained after disassembling the battery, as provided in this application.

[0010] The above-mentioned figures include the following reference numerals: 10, tab; 11, first region; 12, second region. Detailed Implementation

[0011] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0012] As analyzed in the background section of this application, existing technologies suffer from the problem that silicon-based anode materials are prone to expansion, leading to a decrease in battery performance. To address this issue, this application provides an anode sheet and a battery.

[0013] According to a typical embodiment of this application, a negative electrode sheet is provided, including a current collector, a negative electrode material layer disposed on the surface of the current collector, and a plurality of tabs 10 connected to one side of the current collector. The material of the negative electrode material layer includes a negative electrode material, which includes a silicon-based material, such as... Figure 1As shown, along the lead-out direction x of the tab 10, the portion of the negative electrode material layer closer to the tab 10 is the first region 11, and the portion farther from the tab 10 is the second region 12. The compaction density of the negative electrode material layer in the first region 11 is less than that in the second region 12. The curve showing the change in mass of the negative electrode material layer with temperature, measured by thermogravimetric analysis, shows that the rate of change between the mass measured at the test endpoint and the mass measured at 800℃ is the floating silicon content in the negative electrode material layer, denoted as 'a'. The compaction density of the negative electrode material layer in the first region 11 is b g / m³. 3 ; a and b satisfy the relationship: 0.13≤a×b×100≤13.6 (I).

[0014] The inventors discovered that a "floating silicon" phenomenon often exists on the surface of silicon-based materials. Due to the lack of sufficient carbon framework structure to constrain them, some silicon particles fail to effectively embed themselves within the pores of amorphous carbon, instead floating on the surface of the negative electrode material to form floating silicon. The presence of this surface floating silicon exacerbates the volume expansion of silicon during lithium intercalation, leading to interfacial delamination between the negative electrode material layer and the current collector, resulting in a significant increase in contact resistance and ultimately affecting the battery's kinetic performance and energy density.

[0015] Using silicon-carbon anodes can improve battery energy density, but silicon material itself is prone to expansion, leading to an increase in dynamic contact resistance (DCR). Tab 10 is a current-carrying component; during charging and discharging, the current density at this location is high, making it susceptible to localized temperature rise. Increased temperature near tab 10 affects the stability of the anode interface and the electrolyte transport state, increasing polarization in this area and negatively impacting the battery's DCR. Reducing the compaction density of the anode material layer near tab 10 can appropriately increase the porosity and electrolyte wettability in this area, enhancing the lithium-ion transport capacity under high current density conditions. This alleviates the localized polarization and impedance increase caused by overcurrent at tab 10, reducing the impact on the battery's DCR. When the floating silicon content 'a' in the negative electrode material layer is high, the volume expansion of silicon during cycling is more pronounced, the electrode pore structure is more easily compressed, the ion transport channels are reduced, and the battery's DCR increases. In order to reduce the impact on the battery's DCR, the compaction density 'b' of the negative electrode material layer in the first region 11 is reduced to increase the pore space, improve lithium-ion transport, and thus alleviate the problem of limited ion transport.

[0016] This application improves the battery's kinetic performance and energy density by comprehensively controlling the relationship between the floating silicon content (a) and the compaction density (b) in a specific region of the negative electrode sheet, as expressed in Equation (I). When Equation (I) is too large, the higher the floating silicon content, the more severe its expansion becomes due to the lack of buffering and constraint from the carbon skeleton. This can easily generate significant interfacial stress during charging and discharging, potentially leading to lattice distortion, reducing the kinetic rate of the lithiation reaction, or increasing the compaction density near the tab 10, hindering the diffusion of lithium ions from the electrolyte into the electrode sheet, thus increasing the battery's DCR. Conversely, when Equation (I) is too small, the lower the silicon content, the lower the specific capacity of the negative electrode sheet, or the smaller the compaction density near the tab 10, the less active material in the negative electrode, resulting in a lower battery energy density. Compared to other ranges, limiting Equation (I) to the specific range of this application effectively adjusts the interaction between the floating silicon content and the compaction density, achieving a balance between suppressing silicon expansion and increasing the energy density of the negative electrode sheet, thereby comprehensively improving the battery's kinetic performance and energy density.

[0017] This application utilizes thermogravimetric (TG) analysis to accurately determine the content of floating silicon in the negative electrode material layer. Taking silicon-carbon materials as an example, the nano-silicon embedded with porous carbon in silicon-carbon materials typically has a size ≤2nm and exhibits extremely high reactivity. Surface floating silicon, lacking the spatial constraints of a carbon skeleton, is typically larger and has lower reactivity. During TG analysis of silicon-carbon materials, as the carbon material dissolves between 500 and 600°C, the highly active nano-silicon inside is exposed, combining with oxygen to form SiO2. Surface floating silicon, due to its larger size and lower reactivity, typically requires temperatures above 800°C to react with oxygen and form SiO2. Therefore, by testing the mass of the negative electrode material layer at 800°C and the rate of change of mass at the test endpoint, the floating silicon content 'a' in the negative electrode material layer can be determined. The mass measured at the test endpoint refers to the sample mass at which the temperature no longer changes in the TG analysis curve. For the negative electrode material layer in the first region 11 of this application, the test endpoint is typically the moment when the temperature changes to 1000–1200°C.

[0018] Specifically, the floating silicon content 'a' in the negative electrode material layer can be tested using the following method: Discharge the battery to 2.5V at 0.33C, remove the empty battery, disassemble the negative electrode sheet, soak the negative electrode sheet in dimethyl carbonate (DMC) solution for 4 hours, then air dry it. Scrape off the negative electrode material layer from the current collector surface and spread it evenly on the bottom of the crucible. Then place the crucible in the sample chamber of the TGA instrument. During the test, a gas (such as air or oxygen) is introduced at a certain flow rate to ensure that the sample is tested in a controlled atmosphere. Raise the temperature to 105℃ at a certain heating rate (such as 10–20℃ / min) and hold for 5–10 minutes to remove moisture or other volatile components from the sample. Then, continue heating at the same rate to 800℃ and record the sample weight as m1. Then, raise the temperature to 1000℃–1200℃ at the same rate and record the sample weight as m2. Throughout the heating process, the instrument continuously records the mass change of the sample, obtaining a mass-temperature curve, i.e., the TG curve. The content of floating silicon, 'a', was determined by analyzing the changes in mass. .

[0019] In this application, the floating silicon content *a* in the negative electrode material layer can be controlled by adjusting the pore volume, microporosity, and volume ratio of silane to nitrogen of the porous carbon. The larger the pore volume and microporosity, the larger *a*; the larger the volume ratio of silane to nitrogen, the larger *a*. The compaction density *b* g / m³ of the negative electrode material layer in the first region 11 is also mentioned. 3 The thickness of the negative electrode material layer can be obtained by dividing the areal density of the negative electrode material layer in the first region 11 by the thickness of the negative electrode material layer in the first region 11. The method for testing the thickness of the negative electrode material layer includes the following steps: the battery is discharged to 2.5V at 0.33C, the empty battery is taken out, the electrode is disassembled, the electrode is soaked in dimethyl carbonate (DMC) solution for 4 hours, and then dried; the disassembled electrode is subjected to cross-sectional polishing (CP) treatment, and the thickness of the active material layer at the cross-section is obtained using SEM (scanning electron microscope).

[0020] The test method for the compaction density b of the negative electrode material layer in the first region 11 includes: (1) Pretreatment: Discharge the battery to 2.5V at 0.33C, take the empty battery, disassemble the negative electrode sheet, soak the negative electrode sheet in dimethyl carbonate (DMC) solution for 4h; air dry; (2) Use a punching machine to punch the pretreated positive electrode sheet into rectangular sheets of fixed area, the area is recorded as S0. In order to ensure the accuracy of the test, take three rectangular sheets as parallel samples, and then use an electronic balance to weigh the mass of the three rectangular sheets respectively. The mass of each rectangular sheet is recorded as M1, and the decimal point is retained to four places. Take the average value; and use a micrometer to measure the thickness of the three rectangular sheets respectively (measure the thickness at 8 locations for each electrode sheet and take the average value, denoted as H1), retaining four decimal places, and take the average value of the three thicknesses; finally, drop an appropriate amount of deionized water onto each of the three rectangular sheets, gently wipe off the coating on the rectangular sheets with lint-free paper to expose the copper foil, let stand at room temperature (dry) for 10 minutes, and after the copper foil is dry, weigh the three copper foil sheets respectively, record it as M0, retain four decimal places, and take the average value; and use a micrometer to measure the thickness of the three copper foils respectively, record it as H0, retain one decimal place, and take the average value. Calculate the compaction density of the negative electrode material layer in the first region 11 according to the following formula:

[0021] (1)

[0022] (2)

[0023] Where A is the areal density of the negative electrode material layer, in g / cm³. 2 M1 is the total mass of the fixed-area electrode, in mg; M0 is the mass of the foil material coated in the fixed-area region, in mg; S0 is the fixed area of ​​the electrode, in cm². 2 H1 is the electrode thickness in µm; H0 is the copper foil thickness in µm.

[0024] The sampling method for the rectangular sheet in the above test method is as follows: the negative electrode sheet is cut with a switch, and the side closest to the tab 10 is the electrode area corresponding to the first region 11. A rectangular strip with a width h1 of the first region 11 and a length of 100mm is cut along the vertical direction of the side of the tab 10; the remaining area is the electrode area corresponding to the second region 12.

[0025] In this application, the compaction density b of the negative electrode material layer in the first region 11 is controlled by adjusting the rolling pressure and the roller spacing during the electrode rolling process. The higher the rolling pressure, the larger b is; the smaller the roller spacing, the larger b is. In some embodiments of this application, the thickness of the first region 11 in the negative electrode material layer is 0.1 μm to 10 μm; the thickness of the second region 12 is 40 μm to 100 μm.

[0026] Specifically, the value of a×b×100 can be 0.4, 0.7, 1, 1.5, 2, 4, 6, 8, 10, 12, 14, 15, etc., and is not limited here. In some preferred embodiments of this application, 0.7≤a×b×100≤2.7. Controlling the value of the above relationship within the above range can better balance the kinetic performance and energy density of the negative electrode.

[0027] In some embodiments of this application, 'a' is 0.001 to 0.1, specifically 0.001, 0.005, 0.01, 0.015, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1, and is not limited herein. Compared to other ranges, limiting the floating silicon content 'a' to the above range is beneficial for suppressing the expansion of the negative electrode, improving lithium-ion transport efficiency, reducing DCR, and also for increasing the specific capacity of the negative electrode and improving the energy density of the battery. Preferably, 'a' is 0.005 to 0.02.

[0028] In some embodiments of this application, b is 1.1 to 1.7, specifically 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, or 1.7, and is not limited herein. Compared to other ranges, limiting b to the above range is beneficial for the negative electrode to have better DCR and energy density. When b is too large, the compaction density in the region near the tab 10 is too large, hindering the diffusion of lithium ions from the electrolyte into the electrode, resulting in an excessively high DCR of the battery; when b is small, the compaction density in the region near the tab 10 is too small, resulting in too little negative electrode active material in this region and low energy density of the battery. Preferably, b is 1.2 to 1.55.

[0029] In some embodiments of this application, the tabs 10 of the negative electrode are continuously disposed on one side of the current collector, and b is 1.15 to 1.5. The way the tabs 10 are continuously disposed means that the entire edge of the current collector is used as tabs 10, or the tabs 10 are densely and continuously distributed without gaps. The number of tabs 10 is large, the flow path is short, and the use of a smaller compaction density is beneficial to reduce DCR while ensuring energy density.

[0030] In some embodiments of this application, the tabs 10 of the negative electrode are spaced apart on one side of the current collector, and b is 1.25 to 1.58. The way the tabs 10 are spaced apart is that the tabs 10 are distributed at a fixed interval on the edge of the current collector. The number of tabs 10 is small and the flow path is long. Keeping the compaction density of the area near the tabs 10 within the above range is beneficial to improving the energy density of the battery and better balancing dynamic performance and energy density.

[0031] In some embodiments of this application, such as Figure 1As shown, along the lead-out direction x of the tab 10, the width h1 of the first region 11 is 5mm to 8mm. Compared to other ranges, limiting the width h1 of the first region 11 to the above range is beneficial for lithium ions to diffuse from the electrolyte into the electrode, reducing internal resistance, and also beneficial for increasing the energy density of the negative electrode. Specifically, the width h1 of the first region 11 can be 5mm, 6mm, 7mm, 8mm, or any two of the above values.

[0032] In some embodiments of this application, such as Figure 1 As shown, along the lead-out direction x of the tab 10, the width h2 of the second region 12 is 5mm to 15mm. Compared to other ranges, limiting the width h2 of the second region 12 to the above range is beneficial for lithium ions to diffuse from the electrolyte into the electrode, reducing internal resistance, and also beneficial for increasing the energy density of the negative electrode. Specifically, the width h2 of the second region 12 can be 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, or any two of the above values.

[0033] Those skilled in the art will understand that, as Figure 1 As shown, along the lead-out direction x of the tab 10, the width of the negative electrode material layer, that is, the sum of the widths of the first region 11 and the second region 12, is 70 to 150 mm.

[0034] In some embodiments of this application, the ratio of the compaction density of the negative electrode material layers in the first region 11 and the second region 12 is 0.80 to 0.97, specifically 0.80, 0.83, 0.85, 0.88, 0.9, 0.92, 0.95, 0.97, or any two of the above values. Compared to other ranges, limiting the ratio of the compaction density of the negative electrode material layers in the first region 11 and the second region 12 to the above range is beneficial to improving the energy density of the battery and reducing DCR. When the ratio of the compaction density of the negative electrode material layers in the first region 11 and the second region 12 is too large, the diffusion of lithium ions in the negative electrode sheet is more difficult, making it difficult to effectively improve the DCR increase caused by the expansion of silicon-based materials, resulting in a significant increase in DCR. Conversely, when the ratio is too small, there is less active material in the negative electrode material layer, which is detrimental to the energy density of the battery.

[0035] It should be noted that the constituent materials of the negative electrode material layers in the first region 11 and the second region 12 can be the same or different, and this application does not have any special requirements in this regard.

[0036] The negative electrode of this application does not have special requirements for silicon-based materials, as long as they satisfy the relationship (I) above. In some embodiments of this application, the Dv50 of the silicon-based material is 1μm to 15μm. Specifically, the Dv50 of the silicon-based material can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any two of the above values.

[0037] The testing method for the Dv50 of the negative electrode material in the negative electrode material layer includes the following steps: A Malvern 3000 detector is used. After dispersing a sample of appropriate concentration in a suitable liquid, a beam of monochromatic light is passed through the dispersion system. The light is scattered by the particles and distributed at different angles. A multi-element detector receives the values ​​of the scattering patterns at many angles according to a regular pattern. The scattering values ​​are calculated to obtain the ratio of the volume of each particle size to the total volume, thus obtaining the particle size distribution. 0.05g of the negative electrode material is weighed into a 50mL beaker. 3mL of 1% nonylphenol polyoxyethylene ether is added to the beaker as a dispersant, and the mixture is stirred into a paste. Then, 20mL of deionized water is added, and the mixture is stirred with a glass rod. The mixture is then ultrasonically dispersed at 40kHz for 1min. The mixture is stirred continuously with a glass rod for 10 revolutions, and then quickly poured into the test sample cell. The beaker is then rinsed with a wash bottle, and all the rinsing solution is poured into the sample cell. The sample was tested under the following conditions: refractive index (2.42), absorptivity (1%), rotation speed (2000), internal ultrasonic intensity (18%), full-process ultrasound, light blocking (10%~20%), automatic analysis 4 times, and residual (<3%).

[0038] In some embodiments of this application, the silicon-based material is a silicon-carbon material, which has better overall performance and is relatively inexpensive and readily available. In some embodiments, the silicon-carbon material includes silicon particles and a carbon matrix, with at least some of the silicon particles located within the pores of the carbon matrix.

[0039] In some embodiments of this application, the carbon matrix includes amorphous carbon, which can suppress the volume expansion of silicon to a certain extent. Preferably, the mass of amorphous carbon accounts for 1 wt% to 98 wt% of the carbon element mass in the silicon-carbon material. The introduction of amorphous carbon is beneficial to enhancing the overall structural strength of the negative electrode sheet and suppressing material pulverization and shedding caused by volume changes during charging and discharging, while crystalline carbon in the carbon matrix is ​​beneficial to improving the dynamic performance of the battery. More preferably, the mass of amorphous carbon accounts for 5 wt% to 70 wt% of the carbon element mass in the silicon-carbon material.

[0040] It should be noted that, in this application, amorphous carbon refers to carbon materials with a very low degree of graphitization and crystallization, which are approximately amorphous (or lack a fixed shape and periodic structural regularity), such as carbon black. Crystalline carbon has a regular crystal structure, such as diamond, graphite, fullerenes, and carbon nanotubes.

[0041] The test method for the ratio of crystalline carbon to amorphous carbon includes the following steps: (1) Sample preparation: Charge / discharge the battery through the Xinwei equipment. For a fully charged battery, constant current and constant voltage charging is required at a current of 0.10. The voltage range is 2.5 to 4.25V, and the constant voltage cutoff current is 0.05C. For an empty battery, discharge it to 2.5V at a current of 0.1C. Disassemble the empty battery under the condition of qualified dew point and take out the empty negative electrode sheet. (2) Use a blade to scrape the powder off the above negative electrode sheet and test XRD. The ratio of the peak area of ​​the characteristic peak of graphite (the sharp peak near 26.5°) in the measured XRD pattern to the peak area of ​​the characteristic peak (002) of hard carbon (the peak between 20° and 26°) is the ratio of crystalline carbon to amorphous carbon.

[0042] In some embodiments of this application, the specific surface area of ​​the negative electrode material layer is 0.5 m². 2 / g~10m 2 / g. Compared to other ranges, limiting the specific surface area of ​​the anode material layer within the above range is beneficial for improving lithium-ion transport efficiency, battery kinetics, and reducing DCR. Specifically, the specific surface area of ​​the anode material layer can be 0.5m². 2 / g、1m 2 / g、3m 2 / g、5m 2 / g、7m 2 / g、9m 2 / g, 10m 2 / g or the range between any two of the above values.

[0043] The test method for the specific surface area of ​​the negative electrode material layer includes the following steps: The battery is discharged to 2.5V at 0.33C. The empty battery is then removed, and the electrode sheets are disassembled. The electrode sheets are soaked in dimethyl carbonate (DMC) solution for 4 hours and then dried. The negative electrode material layer obtained from the disassembled negative electrode sheet is taken as a sample. A MicroGemini VII 2390 series specific surface area analyzer is used for testing. During the test, the sample undergoes physical adsorption. When the sample adsorption reaches equilibrium, the equilibrium adsorption pressure and the amount of adsorbed gas are measured. The amount of monolayer adsorption of the sample can be calculated according to the BET equation, thereby calculating the specific surface area of ​​the sample. The mass of the empty sample tube after plugging is recorded as M. a Accurate to 0.1 mg. Control the sample volume to 3 / 4 of the bulb volume, weigh the sample tube and record the mass M. b Accurate to 0.1 mg. Degas at 200℃ for 120 min, and weigh to obtain the degassed mass M. c Accurate to 0.1 mg. Install the sample tube onto the instrument, set the test parameters, and perform the test.

[0044] The BET equation is as follows:

[0045]

[0046] in, P Indicates the adsorbate equilibrium pressure; P 0 This represents the saturated vapor pressure of the adsorbate at the adsorption temperature. V This represents the adsorption volume under equilibrium pressure; V m Indicates the saturated adsorption capacity of a single layer; C This represents a constant related to the heat of adsorption, reflecting the strength of the interaction between the adsorbent and the adsorbate.

[0047] Experiments were conducted to determine different relative pressures ( P / P 0 Adsorption amount at ) V ,by right Drawing can be done A straight line is obtained within the range, and its slope and intercept are used to determine the solution. V m and C The specific surface area is then calculated using the following formula. S BET :

[0048]

[0049] in, σ The cross-sectional area of ​​the adsorbate molecule (e.g., 0.162 nm for N2). 2 ), N A Let Avogadro's constant be 1. m For sample quality.

[0050] In some embodiments of this application, the thickness of the negative electrode material layer is 50 μm to 100 μm. Compared to other ranges, limiting the thickness of the negative electrode material layer within the above range is beneficial for the battery to have a more suitable energy density and DCR. Specifically, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or any two of the above values.

[0051] In addition to silicon-based materials as anode active materials, the anode material layer can also include other anode active materials, such as artificial graphite, natural graphite, hard carbon, etc.

[0052] The negative electrode material layer may also include additives such as binders and conductive agents, and there are no particular restrictions on the specific types.

[0053] In some embodiments of this application, the negative electrode material layer comprises, by weight percentage, 95wt% to 97wt% negative electrode active material, 0.55wt% to 2.2wt% conductive agent, and 2.5wt% to 3.5wt% binder.

[0054] In some embodiments of this application, the silicon content in the negative electrode material layer is 1wt% to 20wt%, which makes the battery using the negative electrode have higher capacity and energy density.

[0055] As an example, the negative electrode conductive agent can be one or more of the conventional negative electrode conductive agents such as acetylene black and carbon nanotubes.

[0056] This application does not specifically limit the type of negative electrode binder. In some embodiments, as an example, the binder can be one or more of conventional negative electrode binders such as styrene-butadiene rubber latex (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), and sodium carboxymethyl cellulose (CMC). In this application, the binder is preferably PAA, SBR, and CMC, and the mass ratio of PAA, SBR, and CMC can be (34.38~74.29):(20~59.38):(5~7.14).

[0057] According to another typical embodiment of this application, a method for preparing the above-mentioned negative electrode sheet provided in this application is provided, comprising: step S1, mixing negative electrode active material, conductive agent, binder and solvent to obtain negative electrode slurry; step S2, coating the negative electrode slurry on both sides of the current collector, and drying it to obtain a double-sided coated electrode sheet; scraping one side of the double-sided coated electrode sheet with a blade to obtain a double-sided coated electrode sheet with a first region 11 on one side edge; or, coating the negative electrode slurry on both sides of the current collector, and then rolling it, adjusting the gap (i.e., roller spacing) between the coating roller and the back roller to 75-120 μm and the rolling pressure to 0.5-6T during the rolling process to obtain a double-sided coated electrode sheet with a first region 11 on one side edge; step S3, cutting the double-sided coated electrode sheet near the first region 11 to obtain a negative electrode sheet with multiple tabs 10; wherein, the method for preparing the negative electrode active material comprises: step S1, preparing a pore volume of 0.85-1 cm 3 / g of porous carbon with a microporosity of 85%–96% is prepared for use; Step SA2: using silane as the first precursor, silicon deposition is performed on the porous carbon in nitrogen to obtain the negative electrode material precursor; wherein, the silane introduction rate is 2–5 L / min, the nitrogen introduction rate is 2–25 L / min, the volume ratio of silane to nitrogen is 1:(1–5), the silicon deposition heating rate is 5℃ / min, the temperature is 450–550℃, and the time is 3–9 h; Step SA3: using acetylene as the second precursor, carbon deposition is performed on the negative electrode material precursor in nitrogen to obtain the negative electrode active material; wherein, the acetylene introduction rate is 2–5 L / min, the carbon deposition heating rate is 5℃ / min, the temperature is 550–650℃, and the time is 2–4 h.

[0058] In some embodiments of this application, in step S2, the angle is set to 15° to 30° during the scraping process, the blade feed speed is 0.5 to 2 m / min, and the single scraping depth is 5 to 15 μm.

[0059] In some embodiments of this application, the porous carbon is derived from resin, biomass, coal, coke, sugar, etc. Porous carbon with a suitable pore structure can be obtained through screening.

[0060] According to another typical embodiment of this application, a battery is provided, including a positive electrode, a separator, and a negative electrode, wherein the negative electrode is the aforementioned negative electrode provided in this application.

[0061] This application achieves a balance between suppressing silicon expansion and increasing the energy density of the negative electrode by comprehensively controlling the relationship between the floating silicon content a and the compaction density b in a specific region of the negative electrode sheet according to Equation (I), thereby comprehensively improving the dynamic performance and energy density of the battery.

[0062] In some embodiments of this application, the positive electrode has tabs, and the tabs 10 of the positive electrode and the negative electrode are led out on the same side, with b being 1.15 to 1.5. When the tabs 10 of the positive electrode and the negative electrode are led out on the same side, the current path is shorter, and a smaller compaction density is used, which is beneficial for better balancing the dynamic performance and energy density of the battery.

[0063] In some embodiments of this application, the positive electrode has tabs, and the tabs 10 of the positive electrode and the negative electrode are led out on opposite sides, with b being 1.25 to 1.58. When the tabs 10 of the positive electrode and the negative electrode are led out on opposite sides, the current path is relatively long. Using the compaction density within the above range is beneficial for better balancing the kinetic performance and energy density of the battery.

[0064] In some embodiments of this application, the positive electrode sheet includes a positive electrode material layer, which includes a positive electrode active material. The positive electrode active material includes, but is not limited to, one or more of lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), and lithium nickel cobalt manganese oxide (NCM). This application does not have any special requirements for the positive electrode active material.

[0065] In some embodiments of this application, the positive electrode active material of the positive electrode is lithium nickel cobalt manganese oxide, and b is 1.2 to 1.55. This is because the specific capacity of lithium nickel cobalt manganese oxide ternary materials is high, and they have high energy density. Using a compaction density b within the above range is beneficial to improving the dynamic performance of the battery. When using a positive electrode with lithium nickel cobalt manganese oxide as the positive electrode active material, when the tabs of the positive electrode and the tabs 10 of the negative electrode are led out on the same side, b is preferably 1.2 to 1.5; when using a positive electrode with lithium nickel cobalt manganese oxide as the positive electrode active material, when the tabs of the positive electrode and the tabs 10 of the negative electrode are led out on opposite sides, b is preferably 1.25 to 1.55.

[0066] Because cylindrical battery electrodes experience high stress and are more prone to expansion, in some embodiments of this application, the battery is cylindrical, and b is 1.2 to 1.55. For cylindrical batteries, limiting the compaction density of the negative electrode material layer in the first region 11 to the above range, compared to other ranges, is beneficial to improving the performance of the cylindrical battery.

[0067] Because of the large gap between the electrodes in a prismatic battery, the degree of battery expansion is small. In some embodiments of this application, the battery is a prismatic battery, and b is 1.25 to 1.58. For prismatic batteries, limiting the compaction density of the negative electrode material layer in the first region 11 to the above range, compared to other ranges, is beneficial to improving battery performance.

[0068] The battery in this application is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be used again after being discharged by recharging to activate the active materials.

[0069] Typically, a secondary battery, besides the battery assembly (electrode assembly including positive electrode, negative electrode, and separator), also includes an electrolyte and an outer casing. The electrode assembly and electrolyte are assembled inside the outer casing. During charging and discharging, active ions (such as lithium ions) move back and forth between the positive and negative electrodes, inserting and extracting. The separator, positioned between the positive and negative electrodes, prevents short circuits while allowing active ions to pass through. The electrolyte, located between the positive and negative electrodes, conducts the active ions.

[0070] A positive electrode typically includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which can be any existing publicly disclosed positive electrode active material or a positive electrode active material optimized based on existing materials.

[0071] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive electrode active material, conductive agent, binder and any other components, in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and after drying, rolling, cutting and other processes, the positive electrode sheet can be obtained.

[0072] In this application, the binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. This application does not have any particular limitation on the type of binder for the positive electrode sheet. Specifically, at least one of the following can be used: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC), and sodium alginate.

[0073] This application does not impose any particular restrictions on the positive electrode current collector, as long as it is conductive and will not cause adverse chemical changes in the battery, and can be made of, for example: stainless steel, aluminum, nickel, titanium, sintered carbon; or aluminum or stainless steel that has been surface treated with one of carbon, nickel, titanium, silver, etc.

[0074] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte; it can be selected according to requirements. As an example, the electrolyte in this application can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent; the electrolyte typically includes a lithium salt, and additives may also be added to the electrolyte.

[0075] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP). The concentration of the electrolyte in the electrolyte solution can be 0.5–5 mol / L.

[0076] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0077] In some implementations, as an example, the additive may be a conventional electrolyte additive such as fluoroethylene carbonate (FEC), chloroethylene carbonate (CEC), or vinylene carbonate (VC).

[0078] This application does not impose any particular limitation on the type of diaphragm; any well-known porous diaphragm with good chemical and mechanical stability can be selected. In some embodiments, as examples, the diaphragm can be one of PP, PE, or PP / PF; the diaphragm can also be a structure in which a coating is formed on the surface of a base membrane, wherein the base membrane coating can be one of PP, PE, or PP / PF, and the coating can be an inorganic coating and / or an organic coating. The inorganic coating can be selected from alumina ceramic layers, osmium silicate, etc., and the organic coating can be selected from PVDF, etc.

[0079] As an example, the preparation process of a secondary battery is as follows: the positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. Then, the electrodes are wound or stacked to obtain an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0080] The beneficial effects that this application can achieve will be further illustrated below with reference to embodiments and comparative examples.

[0081] Example 1

[0082] (1) Preparation of silicon-carbon materials:

[0083] Purchase commercially available porous carbon for later use; the pore volume of this porous carbon is 0.96 cm³. 3 / g, with a microporosity of 94%;

[0084] 500g of porous carbon was placed in a rotary kiln and purged with high-purity nitrogen (99.99% purity) at a rate of 1L / min for 2 hours. After purging, the temperature was increased to 500℃ at a rate of 5℃ / min. After reaching the target temperature, silane (99.999% purity) was introduced at a rate of 2L / min, and high-purity nitrogen was introduced at a rate of 2L / min. The temperature was maintained for 3 hours.

[0085] The silane gas was turned off, and the temperature was increased to 600℃ at a rate of 5℃ / min. Acetylene (98%) and high-purity nitrogen were introduced at a rate of 2L / min. After holding at this temperature for 2 hours, the acetylene gas was turned off, and the temperature was allowed to drop naturally to obtain silicon-carbon material.

[0086] (2) Preparation of negative electrode:

[0087] Graphite, silicon-carbon material obtained in step (1), conductive agent SP, conductive agent SWCNT, binder PAA, and binder SBR are dispersed in deionized water at a mass ratio of 83.52:12.48:0.95:0.05:1:2 to obtain a negative electrode slurry. The negative electrode material is coated on both sides of a copper foil, and then dried and rolled sequentially to obtain a double-sided coated electrode sheet with a first region 11 on one side edge (the rolling pressure is controlled at 3.5T and the roller spacing is 100μm during the rolling process). After slitting, a die-cutting device is used to die-cut the double-sided coated electrode sheet near the first region 11, cutting out continuously distributed tabs 10, and then obtaining the following... Figure 1 The negative electrode shown.

[0088] Examples 2 to 20

[0089] The differences from Example 1 are summarized in Table 1.

[0090] Comparative Examples 1 to 4

[0091] The differences from Example 1 are summarized in Table 1.

[0092] Application Example 1

[0093] The negative electrode sheets obtained in the above embodiments and comparative examples were prepared into cylindrical batteries according to the following method, and their electrochemical performance was tested.

[0094] (1) Preparation of the positive electrode:

[0095] LiNi was mixed in a mass ratio of 98.2%:1.1%:0.65%:0.05%. 0.92 Co 0.07 Mn 0.01O2 is uniformly mixed with binder PVDF, conductive agent SP, and conductive agent SWCNT and dispersed in NMP to obtain a positive electrode slurry. This positive electrode slurry is then coated onto aluminum foil to obtain a double-sided coated positive electrode sheet. After rolling and cutting, the positive electrode sheet is obtained. During the preparation of the positive electrode sheet, the areal density is controlled to be 405 g / m³. 2 The compaction density of the positive electrode is 3.55 g / cm³. 3 .

[0096] (2) Preparation of electrolyte:

[0097] EC, EMC, and DEC were mixed in a volume ratio of 1:1:1 to obtain a solvent. Then, 2 wt% VC and 3 wt% FEC were added, followed by fully dried lithium salt LiPF6, to obtain an electrolyte with a lithium salt concentration of 1 mol / L.

[0098] (3) Preparation of the diaphragm:

[0099] The diaphragm is commercially available. Its base membrane is a PE membrane with a thickness of 9μm. One side surface of the base membrane is sequentially provided with an alumina coating with a thickness of 3μm and a PVDF coating with a thickness of 2μm. The other side surface of the base membrane is provided with a PVDF coating with a thickness of 2μm.

[0100] (4) Assembly and formation:

[0101] The positive electrode, separator, and negative electrode prepared in each embodiment or comparative example are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. Then, they are wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, and shaping, a soft-pack cylindrical battery with a specification of 81mm×81mm is obtained.

[0102] DCR testing method:

[0103] The battery was placed in a fixture and a force of 3000N was applied. Then, it was charged at a constant current of 0.33C to 4.25V at room temperature (25°C), and left to rest for 30 minutes. Then, it was discharged at a constant current of 0.33C to 2.5V, and left to rest for 30 minutes. This cycle was repeated 3 times. The discharge capacity Cs of the third discharge was recorded as the basis for load adjustment. The capacity was adjusted to 50% SOC and left to stand in a temperature chamber for 2 hours until thermal equilibrium was reached. Then, a 1C pulse discharge was performed for 18 seconds. After standing for 40 seconds, a 1C pulse discharge was performed for 10 seconds. The DCR value was then calculated according to R=U / I.

[0104] Methods for testing energy density:

[0105] Charge the battery at a constant current of 0.33°C to the upper limit voltage of 4.25V, then charge at a constant voltage until the cutoff current is less than or equal to 0.05C, and then discharge. Repeat the above steps 3 times, and use the discharge energy of the third discharge as the discharge energy E of the battery. Calculate the volume S by measuring the relevant dimensional parameters of the individual cell. Calculate the volumetric energy density according to E / S, with the unit being Wh / L.

[0106] Table 1 shows the floating silicon content a in the negative electrode material layer, the compaction density b of the negative electrode material layer in the first region 11, the relationship a×b×100, the pore volume of porous carbon, the microporosity of porous carbon, the volume ratio of silane to nitrogen, the rolling pressure, and the roller spacing.

[0107] The test results are shown in Table 2 below.

[0108] Table 1

[0109]

[0110] Table 2

[0111]

[0112] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0113] In Examples 1 to 20, the a×b×100 values ​​all meet the range of 0.13 to 13.6, indicating a moderate floating silicon content, minimal volume expansion of the silicon-carbon material, low interfacial stress, moderate lithiation reaction kinetics, numerous ion transport channels, and good DCR performance of the cylindrical battery. Furthermore, the prepared negative electrode sheet has a high specific capacity, moderate compaction density in the region near the tab 10, and high energy density of the cylindrical battery.

[0114] As shown in Examples 1 to 8, when a×b×100 both satisfy the preferred range of 0.7 to 2.7, the cylindrical battery exhibits a lower discharge DCR and a higher volumetric energy density. Specifically, when the floating silicon content a in the negative electrode material layer further satisfies 0.5% to 2%, and the compaction density b of the negative electrode material layer in the first region 11 further satisfies 1.20 g / m³, the battery achieves this optimal condition. 3 ~1.55g / m 3 This helps to suppress the expansion of the negative electrode, improve the lithium-ion transport efficiency, promote the diffusion of lithium ions from the electrolyte into the electrode, reduce the DCR, and also helps to increase the specific capacity of the negative electrode and improve the energy density of the battery.

[0115] As can be seen from Comparative Examples 1 and 2, even if the floating silicon content a in the negative electrode material layer and the compaction density b of the negative electrode material layer in the first region 11 both meet the range, the performance of the cylindrical battery will deteriorate when the value of a×b×100 exceeds the range of 0.13 to 13.6. When a×b×100>13.6, the discharge DCR increases significantly, and when a×b×100<0.13, the volumetric energy density decreases.

[0116] As can be seen from Comparative Examples 3 and 4, when the floating silicon content a in the negative electrode material layer and the compaction density b of the negative electrode material layer in the first region 11 both exceed the range, and the value of a×b×100 also exceeds the range of 0.13 to 13.6, the performance of the cylindrical battery will further deteriorate.

[0117] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A negative electrode sheet, characterized in that, The device includes a current collector, a negative electrode material layer disposed on the surface of the current collector, and a plurality of tabs (10) connected to one side of the current collector. The material of the negative electrode material layer includes a negative electrode material, which includes a silicon-based material, and the silicon-based material is a silicon-carbon material. Along the lead-out direction of the tabs (10), the portion of the negative electrode material layer close to the tabs (10) is a first region (11), and the portion of the negative electrode material layer away from the tabs (10) is a second region (12). The compaction density of the negative electrode material layer in the first region (11) is less than the compaction density of the negative electrode material layer in the second region (12). The curve of the mass change of the negative electrode material layer with temperature was obtained by thermogravimetric analysis. In the curve, the change rate of the mass measured at the test endpoint and the mass measured at 800℃ is the floating silicon content in the negative electrode material layer, denoted as a. The compaction density of the negative electrode material layer in the first region (11) is bg / m³. 3 ; The relationship between a and b is: 0.13≤a×b×100≤13.6 (I), where a is 0.001~0.1 and b is 1.1~1.

7.

2. The negative electrode sheet according to claim 1, characterized in that, 0.7≤a×b×100≤2.

7.

3. The negative electrode sheet according to claim 2, characterized in that, The tabs (10) of the negative electrode are continuously disposed on one side of the current collector, and the value of b is 1.15 to 1.5; or, The tabs (10) of the negative electrode are spaced apart on one side of the current collector, and the value of b is 1.25 to 1.

58.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, Along the lead-out direction of the tab (10), the width h1 of the first region (11) is 5mm to 8mm; and / or, Along the lead-out direction of the tab (10), the width h2 of the second region (12) is 5mm to 15mm.

5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The ratio of the compaction density of the negative electrode material layer in the first region (11) to that in the second region (12) is 0.80 to 0.

97.

6. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The Dv50 of the negative electrode material is 1μm to 15μm.

7. The negative electrode sheet according to claim 6, characterized in that, The silicon-carbon material comprises silicon particles and a carbon matrix, with at least a portion of the silicon particles located within the pores of the carbon matrix.

8. The negative electrode sheet according to claim 7, characterized in that, The carbon matrix includes amorphous carbon; the mass of the amorphous carbon accounts for 1 wt% to 98 wt% of the mass of carbon in the silicon-carbon material.

9. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The specific surface area of ​​the negative electrode material layer is 0.5 m². 2 / g~10m 2 / g; and / or, The thickness of the negative electrode material layer is 50μm to 100μm.

10. The negative electrode sheet according to claim 9, characterized in that, The thickness of the first region (11) in the negative electrode material layer is 0.1 μm to 10 μm; and / or the thickness of the second region (12) is 40 μm to 100 μm.

11. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The silicon content in the negative electrode material layer is 1wt% to 20wt%.

12. A battery comprising a positive electrode, a separator, and a negative electrode, characterized in that, The negative electrode is the negative electrode according to any one of claims 1 to 11.

13. The battery according to claim 12, characterized in that, The positive electrode has tabs (10). The tabs (10) of the positive electrode and the tabs (10) of the negative electrode are led out on the same side, and b is 1.15~1.5; or, The tabs (10) of the positive electrode and the tabs (10) of the negative electrode are led out on opposite sides, and the value of b is 1.25 to 1.

58.

14. The battery according to claim 13, characterized in that, The positive electrode sheet includes a positive electrode material layer, and the positive electrode material layer includes a positive electrode active material, wherein the positive electrode active material is selected from one or more of lithium iron phosphate, lithium manganese iron phosphate, and lithium nickel cobalt manganese oxide.

15. The battery according to claim 14, characterized in that, The positive electrode active material is lithium nickel cobalt manganese oxide, and the value of b is 1.2 to 1.

55.

16. The battery according to claim 12, characterized in that, The battery is a cylindrical battery, and b is 1.2 to 1.55; or, The battery is a prismatic battery, and b is 1.25 to 1.58.

Citation Information

Patent Citations

  • Battery pole piece, preparation method and lithium ion battery

    CN116259708A

  • Negative plate and battery

    CN116741931A